Breast self-examination practice and predictors among female secondary school teachers in Addis Ababa, Ethiopia: using the health belief model - Bisrat Tewelde; Mulugeta Tamire; Mirgissa Kaba (BMC, 2022)
Abstract Background Breast cancer is the most frequently diagnosed reproductive organ cancer among women in Ethiopia. Even though breast self-examination (BSE) is shown to be the least expensive, less time-consuming, and non-invasive screening method, the practice of breast self-examination in Ethiopia is poor. Therefore this study aimed to assess breast self-examination practice and predictors among female secondary school teachers using the Health Belief Model. Materials and methods An institution-based, cross-sectional study was conducted among 589 female secondary school teachers in Addis Ababa, Ethiopia. A self-administered questionnaire containing socio-demographic characteristics, sources of information, knowledge, perception on breast self-examination, and BSE practice was prepared based on the Champion's revised Health Belief Model and used as a data collection instrument. Multi-variable binary logistic regression was employed to identify the predictors of breast self-examination practice with significance set at p < 0.05 by controlling possible confounders. Result Breast self-examination was practiced by 43.6% of female secondary school teachers. Television and radio were the commonest sources of information about breast cancer and breast self-examination. Personal history of breast problem (AOR 3.27, 95% CI 1.13-9.45), teaching experience (AOR 2.46, 95% CI 1.33-4.56), knowledge (AOR 1.06, 95% CI 1.01-1.12) and perceived self-efficacy (AOR 1.07, 95% CI 1.01-1.12) were significantly associated with BSE practice. Conclusion The practice of breast self-examination was found to be low. Perceived self-efficacy, personal history of breast problems, and the knowledge level of female teachers were factors associated with the practice of BSE. This suggests the need for educational programs to enhance knowledge regarding breast cancer and improve the practice of breast self-examination.